2019
DOI: 10.1093/nargab/lqz003
|View full text |Cite
|
Sign up to set email alerts
|

Open chromatin structure in PolyQ disease-related genes: a potential mechanism for CAG repeat expansion in the normal human population

Abstract: The human genome contains dozens of genes that encode for proteins containing long poly-glutamine repeats (polyQ, usually encoded by CAG codons) of 10Qs or more. However, only nine of these genes have been reported to expand beyond the healthy variation and cause diseases. To address whether these nine disease-associated genes are unique in any way, we compared genetic and epigenetic features relative to other types of genes, especially repeat containing genes that do not cause diseases. Our analyses show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…For example, decreased nucleosome occupancy likely promotes large-scale GAA repeat expansion in yeast (367). Consistently, bioinformatic analysis revealed that, in human cells, expandable CAG repeats are located in open chromatin regions, unlike stable CAG repeats (471).…”
Section: Role Of the Chromatin Environment In Repeat Instabilitymentioning
confidence: 72%
See 1 more Smart Citation
“…For example, decreased nucleosome occupancy likely promotes large-scale GAA repeat expansion in yeast (367). Consistently, bioinformatic analysis revealed that, in human cells, expandable CAG repeats are located in open chromatin regions, unlike stable CAG repeats (471).…”
Section: Role Of the Chromatin Environment In Repeat Instabilitymentioning
confidence: 72%
“…Several pieces of evidence support this idea. First, tandem repeat loci (but not the lengths of the repeats) are conserved in related species (471,485). At least some of these repeats seem to be actively maintained (486), which indicates that the existence of tandem repeats in these loci could be advantageous from an evolutionarystandpoint.Sometimes,tandemrepeatsitesevenevolveindependently in homologous genes (132).…”
Section: What Could Be the Advantages Of Having So Many Tandem Repeatmentioning
confidence: 99%
“…To this end, we used a large-scale dataset including multiple ChIP-seq profiles for transcription factors (TFs) and histone modifications (HMs) in A549 cells (Schreiber et al, 2020). Since for A549 cells we also have pre- and post-SARS-CoV-2 infection data, it allowed us to examine the ‘epigenetic signature’ (Sorek et al, 2019) (relative enrichment of TFs and HMs) around the TEs that are up-regulated post-infection of SARS-CoV-2 and IAV (Figure 3 and S3).…”
Section: Resultsmentioning
confidence: 99%
“…This reflects a common feature for polyQ disease-related genes that share a very active profile enriched in active marks and depleted in repressive marks in unaffected individuals. It has been suggested that an open chromatin state could be the cause of genomic instability, and in this sense, the heterochromatinization process can be considered as a protective mechanism from acquiring more mutations [56]. Finally, recent studies revealed a link between 3D genome folding and several expansion disorders in which genes are placed at the boundaries between topologically associating domains (TADs) that are highly enriched on CpG islands, suggesting that repeat expansions could disrupt TADs structure, resulting in a reorganization of the genome topology [57].…”
Section: Chromatin Remodeling Of Dm1 Locusmentioning
confidence: 99%